Targeting TLR/IL-1R Signalling in Human Diseases. (8th April 2010) - Loiarro, Maria; Ruggiero, Vito; Sette, Claudio
Abstract : The members of Toll-like receptor/Interleukin (IL)-1 receptor (TLR/IL-1R) superfamily play a fundamental role in the immune response. These receptors detect microbial components and trigger complex signalling pathways that result in increased expression of multiple inflammatory genes. On the other hand, an aberrant activation of TLR/IL-1R signalling can promote the onset of inflammatory and autoimmune diseases, raising the interest in the development of therapeutic strategies for the control of their function. In this review, we illustrate the structural and functional features of TLR/IL-1R proteins and discuss some recent advances in the approaches undertaken to develop anti-inflammatory therapeutic drugs. In particular, we will focus on inhibitors, such as decoy peptides and synthetic mimetics, that interfere with protein-protein interactions between signalling molecules of the TLR/IL-1R superfamily. Given their central role in innate and adaptive immune responses, it is foreseen that pharmaceutical modulation of TLR/IL-1R signalling pathways by these drugs might yield clinical benefits in the treatment of inflammatory and autoimmune diseases.